Modelling minicab drivers' disordered behaviour for choosing passenger and destination in Akure, Nigeria - Adetayo Olaniyi Adeniran; Olorunfemi Samuel; Njoku Ikpechukwu (Institute of Advanced Engineering and Science, 2022)
This study investigated the disordered behaviour of minicab drivers for choosing passenger and destination in Akure using the multinomial model and nested logit model respectively. Information was gathered by the distribution of questionnaires to minicab drivers plying the Federal University of Technology Akure (FUTA) North gate to the Oja-Oba axis in Akure, Nigeria. The objectives were to validate the performance of logit models; to identify the major parameters for selecting passenger and destination by disordered minicab drivers, and to examine the interrelationships of variables employed. Primary data was obtained from 314 respondents. The study found that the nested logit model gives a better utility value than the multinomial logit model with ρ02 = 0.48 more than ρc2 = 0.46 which justifies the assertion. Also, the major parameters for selecting passengers and destination by disordered minicab drivers in Akure are transport rates variable, distance variable, and travel time variable. The study recommends that an accurate pricing policy of minicab operation should be efficiently formulated, implemented, and enacted to prevent overcharging and undercharging.